Influence Of Knowledge Sharing and Information Technology Innovation on Employees Performance at Batamindo Industrial Park - Saut Pin Tub Ipar Saragih; Harisno Harisno (CommIT (Communication and Information Technology) Journal, 2015)
This study aims to measure the effects of knowledge sharing behavior and the level of informa- tion technology innovation on  employee  performance  on electronic manufacturing company located in Bata- mindo Industrial Park. In this article, the authors use research design methods that are associative through survey by distributing questionnaires to the respondents at random. Then, a mathematical model is established through multivariate regression where  the  interaction  of the  independent  variables  and  dependent  variable  is established. As the results, the study concludes that knowledge sharing behavior partially has no significant effects on employee performance but has significant effect on the level of information technology innovation to performance and simultaneously both variables have a significance effect to employee  performance.